Exercise Restores Hypothalamic Health in Obesity by Reshaping the Inflammatory Network - Lucio Della Guardia; Roberto Codella (MDPI AG, 2023)
Obesity and overnutrition induce inflammation, leptin-, and insulin resistance in the hypothalamus. The mediobasal hypothalamus responds to exercise enabling critical adaptions at molecular and cellular level that positively impact local inflammation. This review discusses the positive effect of exercise on obesity-induced hypothalamic dysfunction, highlighting the mechanistic aspects related to the anti-inflammatory effects of exercise. In HFD-fed animals, both acute and chronic moderate-intensity exercise mitigate microgliosis and lower inflammation in the arcuate nucleus (ARC). Notably, this associates with restored leptin sensitivity and lower food intake. Exercise-induced cytokines IL-6 and IL-10 mediate part of these positive effect on the ARC in obese animals. The reduction of obesity-associated pro-inflammatory mediators (e.g., FFAs, TNFα, resistin, and AGEs), and the improvement in the gut-brain axis represent alternative paths through which regular exercise can mitigate hypothalamic inflammation. These findings suggest that the regular practice of exercise can restore a proper functionality in the hypothalamus in obesity. Further analysis investigating the crosstalk muscle-hypothalamus would help toward a deeper comprehension of the subject.